Stream order and connectivity affect phosphorus distribution in plain river network. Issue 1 (1st January 2020) - Lyu, Huihua; Zhou, Feng; Li, Na
ABSTRACT: The order and connectivity of streams influence phosphorus distribution extensively. In this work, the space-and-time variabilities of total phosphorus (TP), particulate phosphorus (PP), total dissolved phosphorus (TDP), dissolved reactive phosphorus (DRP), and dissolved unreactive phosphorus (DUP) in streams of three orders (Ⅰ, Ⅱ, ⅡⅠ) were analyzed during each spring of 2016-2018 in a plain river network area, China. The results show that: ① PP was the main form of TP and DRP was the main form of TDP. ② The average concentrations of phosphorus in the order Ⅰ streams were significant larger than those in the order ⅡⅠ The concentrations of TP, PP, TDP, and DRP in the poor-connected streams were considerably higher than those in the well-connected streams. Therefore, it is essential to implement effective practices to improve the protection and appropriate connectivity of small streams in plain river network areas.